Inhibition of Tankyrases Induces Axin Stabilization and Blocks Wnt Signalling in Breast Cancer Cells - Bao, Renyue; Christova, Tania; Song, Siyuan; Angers, Stephane; Yan, Xiaojun; Attisano, Liliana (PloS one, 2012)
Constitutive Wnt signalling is characterized by excessive levels of β-catenin protein and is a frequent occurrence in cancer. APC and Axin are key components of the β-catenin destruction complex that acts to promote β-catenin degradation. The levels of Axin are in turn controlled by tankyrases, members of the PARP-family of poly-ADP-ribosylation enzymes. In colorectal cancer cells, which typically harbor APC mutations, inhibition of tankyrase activity promotes Axin stabilization and attenuates Wnt signalling. Here, we examined the effect of inhibiting tankyrases in breast cancer cells with normal APC. We show that application of the small molecule tankyrase inhibitor, XAV939 or siRNA-mediated abrogation of tankyrase expression increases Axin1 and Axin2 protein levels and attenuates Wnt-induced transcriptional responses in several breast cancer lines. In MDA-MB-231 cells, inhibiton of tankyrase activity also attenuate Wnt3a induced cell migration. Moreover, in both MDA-MB-231 and colorectal cancer cells, XAV939 inhibits cell growth under conditions of serum-deprivation. However, the presence of serum prevents this growth inhibitory effect, although inhibition of Wnt-induced transcriptional and migratory responses was maintained. These results indicate that stabilization of Axin by inhibition of tankyrases alone, may not be an effective means to block tumor cell growth and that combinatorial therapeutic approaches should be considered.